Surgical treatment for Bell's palsy - review - Małgorzata Staszkiewicz (Wiedza Medyczna, 2022)
Introduction: Bell's palsy is a peripheral, unilateral facial nerve palsy of sudden onset and an unknown cause. The diagnosis is primarily based on clinical examination, but in some patients performing electrophysiological tests, i.e. ENoG and EMG, can be recommended for prognostic purposes. Glucocorticoids are the mainstay of treatment in Bell's palsy, whereas surgical treatment remains controversial.Objectives and methods: Review of literature concerning the relevance of facial nerve decompression for Bell's palsy, its techniques and efficacy, as well as patient's eligibility criteria for surgical treatment. Only publications in English were included.Results: In AAO-HNS guidelines there is no recommendation for surgical treatment in Bell's palsy or against it. The assumption that facial nerve in this entity becomes compressed in the narrowest portion of the Fallopian canal, i.e. meatal foramen, can be the rationale for facial nerve decompression in this segment. The optimal surgical exposure of this portion of the facial nerve canal is provided by the middle cranial fossa approach, although the efficacy of facial nerve decompression via the transmastoid approach has also been reported. Most surgeons consider the degeneration of >90% of facial nerve fibers shown in ENoG the eligibility criterion for surgical treatment in Bell's palsy. There is no consensus on when facial nerve decompression after the onset of Bell's palsy should be performed.Conclusions: Observations show that facial nerve decompression should be considered, if a patient fulfills clinical and electrophysiological criteria. As long as high level quality evidence lacks, clinicians' attitude towards surgical treatment for Bell's palsy will remain ambivalent.